(untitled) (International Seminar on Syariah and Law (INSLA), 2020)
This article explains the order of the position of mujtahids, books and main terminologies (muṣṭalaḥāt) in the Shafi‘i school of Islamic jurisprudence (madhhab) as one of the most important methods in interacting with the classical (turāth) texts. This matter is very crucial for students, madhhab researchers, legal practitioners and muftis in order to comprehend the laws and rulings discussed by the Shafi‘iyyah jurists in their works. The application of the method is done on the procedures and approaches taken by the Shafi‘iyyah jurists regarding the impurity of pigs. This writing is qualitative descriptive involving library research through the analysis of documents on the classical texts of Shafi‘i madhhab in particular as well as the writings of relevant contemporary scholars. The results of this study show that the knowledge and understanding in detail about the position of the mujtahids, the order of the books and the meaning of the terminologies used are the important basis while interacting with the classical texts of the Shafi‘i madhhab in order to meet the correct meaning and stand of the madhhab. Without understanding this matter clearly, a fatwa or ruling issued will deviate from the course of the madhhab and therefore cannot be attributed to the madhhab itself. In the issue of impurity of pigs, al-qawl al-mu‘tamad (officially recognized view) in the Shafi‘i madhhab is that pigs are categorized as al-najāsat al-mughallaẓat (severest form of impurity) just like dogs, hence, it is obligatory to wash anything that comes in contact with any component of pigs seven times using pure water, one of them mixed with soil. Theview of Imam al-Nawawi that pigs are not categorised as al-najāsat al-mughallaẓat which needs to be washed more than once is not the conclusive opinion of Shafi‘i madhhab, hence cannot be associated with the madhhab itself. Artikel ini menjelaskan tertib susunan kedudukan ulamamujtahid, kitab dan terminologi (mustalahat) utama dalam mazhab Syafie sebagai antara kaedah utama dalam berinteraksi dengan teks-teks turath mazhab. Mendalami perkara ini sangat penting bagi para penuntut ilmu, pengkaji mazhab, pengamal undang-undang dan mufti bagi memahami sesuatu hukum yang dibincangkan oleh para fuqaha Syafi‘iyyah dalam karya-karya mereka. Aplikasi kaedah dilakukan terhadap tatacara dan manhaj yang diambil oleh fuqaha Syafi‘iyyah dalam hukum kenajisan khinzir. Penulisan ini bersifat kualitatif deskriptif melibatkan kajian kepustakaan melalui analisis dokumen terhadap teks-teks turath fiqh Syafie secara khusus serta penulisan para ulama kontemporari yang berkaitan.Hasil kajian ini menunjukkan bahawa pengetahuan dan kefahaman secarateliti dan terperinci tentang susunan kedudukan ulama mujtahid, tertib dan peringkat susunan kitab dan maksud mustalahat yang digunakan merupakan asas penting ketika berinteraksi dengan teks-teks turath mazhabSyafie agar kefahaman pembaca dan pengkaji selari dengan maksud sebenar pengarang dan pegangan mazhab. Tanpa memahami perkara ini dengan jelas, sesuatu fatwa atau hukum yang dikeluarkan akan menyimpang dari perjalanan mazhab,justeru tidak boleh disandarkan kepada mazhab itu sendiri.Dalam isu kenajisan khinzir, al-qawl al-mu‘tamad mazhab Syafie ialah khinzir dikategorikan sebagai najis mughallazah sama seperti hukum anjing, wajib dibasuh apa-apa yang bersentuh dengan mana-mana bahagian daripada khinzir sebanyak tujuh kali basuhan air mutlak di antaranya air bercampur tanah. Pandangan Imam al-Nawawi yang mengatakan bahawa khinzir bukan dalam kategori najis mughallazahyang perlu diulang basuhannya bukanlah pegangan muktamad mazhab Syafie dan tidak boleh dinisbahkan kepada mazhab.